CONCEPTUAL MAPPING MODEL ACROSS LANGUAGES: A TEST IN VIETNAMESE LANGUAGE - Nguyen, Vi Thong (Trường Đại học Đà Lạt, 2023)
The conceptual metaphor, LOVE IS A JOURNEY, has been identified as a process of mapping based on the Conceptual Metaphor Theory (CMT) proposed by Lakoff and Johnson (1980). However, Ahrens (2002) pointed out several problems that the CMT may encounter, especially in setting parameters to be experimentally tested. Ahrens (2002) proposed the Conceptual Mapping Model (CMM) to investigate metaphor expressions by identifying three mappings between the source domain and the target domain: entities, qualities, and functions. After an analysis, the reason for these mappings, called a mapping principle, is indicated. In particular, the CMM can predict the processing of conceptual metaphors in terms of conventional and novel metaphors. This study is intended to test whether the CMM can perform well across languages through the experimental rates of acceptability and interpretability for different types of metaphors. Fifty Vietnamese native speakers were recruited. Each participant judged (on a Likert scale of 1-7) the levels of acceptability and interpretability of three conceptual metaphors in Vietnamese: LIFE IS A BOOK, HAPPINESS IS LIGHT, and LOVE IS FIRE. Each conceptual metaphor consists of six types of sentences, including (a) Literal pair to B, (b) Conventional metaphor, (c) Literal pair to D, (d) Novel metaphor that follows the mapping principle, (e) Literal pair to F, and (f) Novel metaphor that does not follow the mapping principle. The results of t-tests show that in terms of both acceptability and interpretability, conventional metaphors are ranked higher than novel metaphors. The results also indicate that novel metaphors that follow the mapping principle are rated higher than those that do not. Therefore, the mapping principle can constrain the image schemas so that any image that does not belong to the schemas can affect the processing of metaphors.